Genome- and Transcriptome-Wide Characterization and Expression Analyses of bHLH Transcription Factor Family Reveal Their Relevance to Salt Stress Response in Tomato - Jianling Zhang; Xiaoying Liu; Zuozhen Yin; Tiantian Zhao; Dan Du; Jing Li; Mingku Zhu; Yueying Sun; Yu Pan (Plants)
The bHLH (basic helix–loop–helix) transcription factors function as crucial regulators in numerous biological processes including abiotic stress responses and plant development. According to our RNA-seq analysis of tomato seedlings under salt stress, we found that, although the bHLH gene family in tomato has been studied, there are still so many tomato bHLH genes that have not been identified and named, which will hinder the later study of SlbHLHs. In total, 195 SlbHLHs that were unevenly distributed onto 12 chromosomes were identified from the tomato genome and were classified into 27 subfamilies based on their molecular features. The collinearity between SlbHLHs and interrelated orthologs from 10 plants further revealed evolutionary insights into SlbHLHs. Cis-element investigations of SlbHLHs promotors further suggested the potential roles of SlbHLHs in tomato development and stress responses. A total of 30 SlbHLHs were defined as the differentially expressed genes in response to salt stress by RNA-seq. The expression profiles of selected SlbHLHs were varyingly and markedly induced by multiple abiotic stresses and hormone treatments. These results provide valuable information to further understand the significance and intricacy of the bHLH transcription factor family, and lay a foundation for further exploring functions and possible regulatory mechanisms of SlbHLH members in abiotic stress tolerance, which will be significant for the study of tomato stress resistance and agricultural productivity.